Enterprise Surveys : South Africa Country Profile 2007 - World Bank; International Finance Corporation (Washington, DC, 2014)
The enterprise surveys focus on the many factors that shape the business environment. The country profile for South Africa is based on data from the enterprise surveys conducted by the World Bank. The benchmarks include the averages for the group of countries in Sub-Saharan Africa and the South Africa income group. The qualitative and quantitative data collected through the surveys connect a country s business environment characteristics with firm productivity and performance. The topics covered include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, finance, innovation, labor, and perceptions about obstacles to doing business. Breakdowns by firm size are presented in the appendix along with all indicators used to make the graphs.